Estudo dos desperdícios alimentares em meio escolar - Campos, V. (2011)
In the past few years we have witnessed an increasing concern about the quality of school meals by the World Health Organization, European Union, and the Ministry of Education. Recently the General Directory of Innovation and Curricular Development released a paper to standardize the meal distribution criteria, aiming to guarantee high quality meals. The food waste is a quality parameter of a Food Service. This study is focused on evaluating the food waste in school canteens, through the analysis of the leftovers and plate wastes by school level and protein component. The samples were the 3758 meals served during 20 days in 4 elementary schools. Food produced was weighted, as well as the leftovers and the plate wastes, and with those values it was calculated the leftover and the plate waste percentage. The average leftover percentage was 7% and the average plate waste was 31%. No significant differences were found between school level, or the protein component.